Disability and migration: new alliances for inclusion - Francesca Marone; Francesca Buccini (University of Bologna, 2020)
The presence on the territory of children, young people and adults of foreign origin, migrants or second generation migrants, with disabilities represents, an increasingly concrete and complex reality at the same time. The double condition migrant-disabled could trigger social, cultural and educational related issues which complicate the path of inclusion by worsening inequalities, discrimination and social exclusion. Faced with the support that the school offers to pupils with disabilities and their families, the educational institutions ask, in turn, for more support from the territorial services: namely a team work (curricular teachers, support teachers, educators, cultural mediators, child neuropsychiatrists, speech therapists, social workers, parents) able to create the appropriate mediation strategies aimed at promoting meetings and dialogues. In the light of these considerations, the following contribution intends to propose a reflection on the need to design, from the point of view of reception and social and educational inclusion, new training paths in which the skills of teachers and operators intersect and enrich each other in daily practice, experimenting innovative methodologies responding to the new challenges of inclusion.